Microbial communities associated with thermogenic gas hydrate-bearing marine sediments in Qiongdongnan Basin, South China Sea - Liu, Siwei; Yu, Shan; Lu, Xindi; Yang, Hailin; Li, Yuanyuan; Xu, Xuemin; Lu, Hailong; Fang, Yunxin (Frontiers in Microbiology, 2022)
Biogenic and thermogenic gas are two major contributors to gas hydrate formation. Methane hydrates from both origins may have critical impacts on the ecological properties of marine sediments. However, research on microbial diversity in thermogenic hydrate-containing sediments is limited. This study examined the prokaryotic diversity and distributions along a sediment core with a vertical distribution of thermogenic gas hydrates with different occurrences obtained from the Qiongdongnan Basin by Illumina sequencing of 16S rRNA genes as well as molecular and geochemical techniques. Here, we show that gas hydrate occurrence has substantial impacts on both microbial diversity and community composition. Compared to the hydrate-free zone, distinct microbiomes with significantly higher abundance and lower diversity were observed within the gas hydrate-containing layers. Gammaproteobacteria and Actinobacterota dominated the bacterial taxa in all collected samples, while archaeal communities shifted sharply along the vertical profile of sediment layers. A notable stratified distribution of anaerobic methanotrophs shaped by both geophysical and geochemical parameters was also determined. In addition, the hydrate-free zone hosted a large number of rare taxa that might perform a fermentative breakdown of proteins in the deep biosphere and probably respond to the hydrate formation.